Association of rs4648551 polymorphism in p73 gene in Iranian woman with idiopathic recurrent pregnancy loss - Somayeh Tabasi; Seyed Mostafa Hoseini (Mashhad University of Medical Sciences, 2020)
Introduction: Recurrent pregnancy loss (RPL) is defined as the repeated occurrence of 2 or more miscarriages before 20th week of gestation. RPL is a multifactorial disorder and genetic defects are considered as one of the major risk factors for recurrent miscarriage. Regarding to the effective role of p73 gene in the process of primary blastocyst division and protection of germ cells, it seems that rs4648551 polymorphism in this p73 gene be associated with the occurrence of spontaneous abortion symptoms. This study was performed with aim to evaluate the frequency of this polymorphism between two groups of Iranian women with idiopathic recurrent miscarriage and healthy women. Methods: This descriptive case-control study was performed in 2015-2016 on 90 patients with history of 2 consecutive idiopathic recurrent spontaneous miscarriages compared to 110 healthy women who had at least two successful pregnancies as controls. DNA was extracted by RGDE procedure and genotyping was performed by Tetra ARMS technique. Data were analyzed by SPSS software (version 22) and Chi-square test. p < 0.05 was considered statistically significant. Results: In SNP rs4648551(A<G), the frequency of GG, CC and GC alleles in p73 gene in the control group were 11.81%, 69.09% and 19.09%, respectively and in the RPL group were 31.11%, 46.67% and 22.22%, respectively; the difference was statistically significant (p < 0.05). But, the value of allelic difference between the patient and control groups was calculated as 0.066 which was not significant. According to the results, the dominant heredity model was suggested (p < 0.05). Conclusion: There is significant association between polymorphism rs4648551 and idiopathic recurrent abortions.